Pengaruh Kualitas Pelayanan Terhadap Word Of Mouth Yang Dimediasi Oleh Kepercayaan Pelanggan - Rahmah, Siti; Sari, Nilam Anggar; Suprapto, Heru; Akbar, Ali (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2024)
Cars are a means of transportation that is widely used in everyday life, but not everyone can afford a car, which is quite expensive. Therefore, companies have emerged that offer car rental services to take advantage of this opportunity. The object of this research is the Raditya Transport car rental service in Tenggarong which has become the main choice for renting four-wheeled vehicles. The aim of this research is to find out how service quality management builds Word of Mouth (WOM) among customers which is mediated by customer trust. This research data was collected through a questionnaire with a total sample of 74 respondents studied. The analytical method used in this research uses Structural Equation Modeling (SEM) Partial Least Square (PLS). The research results show that (1) service quality has a positive effect on word of mouth at Raditya Transport, (2) trust has a positive effect on word of mouth at Raditya Transport, (3) service quality has a positive effect on trust in Raditya Transport, and (4) Service quality has a positive effect on word of mouth through trust as a mediating variable in Raditya Transport.